1974
DOI: 10.1002/ijc.2910130517
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐mediated and humoral immunity studies of murine and hamster sarcoma virus‐induced producer and non‐producer tumors in syngeneic animals

Abstract: 5510 Nicholson, Kensington, Md.; and Miirine sarcoma virus ( M S V ) -induced transformed tumor cells, which are releasers and non-releasers of virus, were investigated by transplantation immunity and a variety of serological assays. Transplantation immunity demonstrated that tumor-associated transplantation antigens could be detected on producer cells and were also apparent, but to a lesser degree, on non-releaser cells of BALBjc mouse origin. Some lymphocyte inicrocytotoxicity tests employing hamster M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1975
1975
1982
1982

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This report was contradicted, however, by the results of Ting and Herberman (45) employing the radiolabeled antibody technique. Similarly, in the case of mouse cells transformed by the nonproducer murine sarcoma virus (MSV), nonvirion, virus-specific tumor surface antigens could not be demonstrated by immunofluorescence or by lymphocyte cytotoxicity tests in vitro -and evidence for isograft resistance based on such surface antigens was not firm (46). This, too, was countered by serologic immunoferritin studies which indicated the presence of such an antigen in small amounts (47).…”
Section: Discussionmentioning
confidence: 85%
“…This report was contradicted, however, by the results of Ting and Herberman (45) employing the radiolabeled antibody technique. Similarly, in the case of mouse cells transformed by the nonproducer murine sarcoma virus (MSV), nonvirion, virus-specific tumor surface antigens could not be demonstrated by immunofluorescence or by lymphocyte cytotoxicity tests in vitro -and evidence for isograft resistance based on such surface antigens was not firm (46). This, too, was countered by serologic immunoferritin studies which indicated the presence of such an antigen in small amounts (47).…”
Section: Discussionmentioning
confidence: 85%
“…There exist numerous methods of potential value for detecting antibodies to tumor antigens in xenogeneic antisera prepared against cellular antigens (Ting and Herberman, 1976;Herberman, 1977). The array of technologies employed previously includes cytotoxicity (Schultz et al, 1975;Fritz e et al, 1976, Rosenberg et al, 1977, complement fixation (Lewis et al, 1969;Wood and Barth, 1974;Sabin and Tarro, 1973;Hollinshead et al, 1976;Rogers et al, 1977), isotopic antiglobulin binding assays (Harder and MacKhann, 1968;Sparks et al, 1969), immunofluorescence (Henle and Henle, 1966;Moller, 1961;McCoy et al, 1974) and antibody-dependent cellular cytoxicity (Perlman et al, 1972;Jolley et al, 1976). The discovery by Kronvall et al, (1970) that Staphylococcus aureus protein A (SPA can bind the Fc portion of several mammalian species of IgG provided the basis for development of new immunoassays to detect IgG antibodies and cellular antigens.…”
mentioning
confidence: 99%